Adhesive blood microsampling systems for steroid measurement via LC-MS/MS in the rat - Heussner, Kirsten; Rauh, Manfred; Cordasic, Nada; Menendez-Castro, Carlos; Hübner, Hanna; Rübner, Matthias; Schmidt, Marius; Hartner, Andrea; Rascher, Wolfgang; Fahlbusch, Fabian B. (Steroids, 2017)
INTRODUCTION: Liquid Chromatography Tandem Mass Spectrometry (LC-MS/MS) allows for the direct analysis of multiple hormones in a single probe with minimal sample volume. Rodent-based animal studies strongly rely on microsampling, such as the dry blood spot (DBS) method. However, DBS suffers the drawback of hematocrit-dependence (non-volumetric). Hence, novel volumetric microsampling techniques were introduced recently, allowing sampling of fixed accurate volumes. We compared these methods for steroid analysis in the rat to improve inter-system comparability. EXPERIMENTAL: We analyzed steroid levels in blood using the absorptive microsampling devices Whatman® 903 Protein Saver Cards, Noviplex™ Plasma Prep Cards and the Mitra™ Microsampling device and compared the obtained results to the respective EDTA plasma levels. Quantitative steroid analysis was performed via LC-MS/MS. For the determination of the plasma volume factor for each steroid, their levels in pooled blood samples from each human adults and rats (18weeks) were compared and the transferability of these factors was evaluated in a new set of juvenile (21days) and adult (18weeks) rats. Hematocrit was determined concomitantly. RESULTS: Using these approaches, we were unable to apply one single volume factor for each steroid. Instead, plasma volume factors had to be adjusted for the recovery rate of each steroid and device individually. The tested microsampling systems did not allow the use of one single volume factor for adult and juvenile rats based on an unexpectedly strong hematocrit-dependency and other steroid specific (pre-analytic) factors. DISCUSSION: Our study provides correction factors for LC-MS/MS steroid analysis of volumetric and non-volumetric microsampling systems in comparison to plasma. It argues for thorough analysis of chromatographic effects before the use of novel volumetric systems for steroid analysis.
EVALuna2:34007